The Effects of fertility and male labor supply on female labor force participation in developed and developing countries - ZUBERU, Sumaila (KDI School, 2015)
In any economy the more females get involved in economic activity of any kind, the brighter the chances of that economic to grow rapidly. Female involvement in the labor market enhances their economic power as well as nation’s economic growth, but there are factors that affect the participation rate. Fertility and male labor supply are a few of those factors. This study tried finding out the short run and long run effects of fertility and male labor supply on female labor market involvement using a full sample of 196 developing and developed countries and a sub sample of 130 developing countries between 1974 and 2013. It further found out if there are significant difference(s) between Sub Saharan Africa and other developing countries. The study reveals that fertility has a significantly adverse effect on female labor market involvement in developing countries and a minor effect in developed countries both in the short and long run. Another finding of this research is that male labor supply rate has a significant positive impact on female labor market involvement in the short run both in developed and developing countries but not in the long run. Fertility has a major adverse effect on female labor market involvement in Sub Saharan Africa and an adverse but insignificant effect in other developing countries in the short run. However the results is different in the long run where fertility has insignificantly negative impact in Sub Saharan Africa but has significantly negative impact in other developing countries. Male labor force participation positively affects female labor market involvement in developing countries in the short run.
Thesis(Master) --KDI School:Master of Development Policy,2015